An evaluative study of coaches' communication skills and their relationship to the motor interaction of soccer teams – a field study of some teams in the Algerian league - Kriba , Farid (sports creativity, 2025)
The current study aims to identify the relationship between coaching communication skills and motor interaction in its three dimensions (understanding the role, accepting the role and performing the role) among soccer players in the first and second national professional football tournaments, and the researcher used the descriptive approach with his relational method and formed The sample of 150 players. The researcher used the test of communication skills and the dynamic reaction scale, and he reached: There is a correlation between the coach's communication skills and understanding the role. There is a correlation between the coach's communication skills and acceptance of the role. There is a correlation between the coach's communication skills and the performance of the role.